An Improved N2 Model for Predicting Gas Adsorption in MOFs and using Molecular Simulation to aid in the Interpretation of SSNMR Spectra of MOFs - Provost, Bianca (Université d'Ottawa / University of Ottawa, 2015)
Microporous metal organic frameworks (MOFs) are a novel class of materials formed through self-assembly of inorganic and organic structural building units (SBUs). They show great promise for many applications thanks to record-breaking internal surface areas, high porosity as well as a wide variety of possible chemical compositions. Molecular simulation has been instrumental in the study of MOFs to date, and this thesis work aims to validate and expand upon these efforts through two distinct computational MOF investigations. Current separation technologies used for CO2/N2 mixtures, found in the greenhouse gas-emitting flue gas generated by coal-burning power plants, could greatly benefit from the improved cost-effective separation MOF technology offers. MOFs have shown great potential for CO2 capture due to their low heat capacities and high, selective uptake of CO2. To ensure that simulation techniques effectively predict quantitative MOF gas uptakes and selectivities, it is important that the simulation parameters used, such as force fields, are adequate. We show that in all cases explored, the force field in current widespread use for N2 adsorption over-predicts uptake by at least 50% of the experimental uptake in MOFs. We propose a new N2 model, NIMF (Nitrogen in MoFs), that has been parameterized using experimental N2 uptake data in a diverse range of MOFs found in literature. The NIMF force field yields high accuracy N2 uptakes and will allow for accurate simulated uptakes and selectivities in existing and hypothetical MOF materials and will facilitate accurate identification of promising materials for CO2 capture and storage as well as air separation for oxy-fuel combustion. We also present the results of grand canonical and canonical Monte Carlo (GCMC and canonical MC), DFT and molecular dynamics (MD) simulations as well as charge density analyses, on both CO2 and N,N-dimethylformamide adsorbed in Ba2TMA(NO3) and MIL-68(In), two MOFs with non-equivalent inorganic structural building units. We demonstrate the excellent agreement found between our simulation results and the solid-state NMR (SSNMR) experiments carried out by Professor Yining Huang (Western University) on these two MOFs. Molecular simulation enables discoveries which complement SSNMR such as the number, distribution and dynamics of guest binding sites within a MOF. We show that the combination of SSNMR and molecular simulation forms a powerful analytical procedure for characterizing MOFs, and this novel set of microscopic characterization techniques allows for the optimization of new and existing MOFs.
Keywords: MOF; Nitrogen; Molecular simulation; Solid-state NMR; Parameterization; Carbon capture